IL-15 promotes self-renewal of progenitor exhausted CD8 T cells during persistent antigenic stimulation - Lee, Junghwa; Lee, Kyungmin; Bae, Hyeonjin; Lee, Kunhee; Lee, Solhwi; Ma, Junhui; Jo, Kyungjo; Kim, Ijun; Jee, ByulA; Kang, Minyong; Im, Se Jin (Frontiers in Immunology, 2023)
In chronic infections and cancer, exhausted CD8 T cells exhibit heterogeneous subpopulations. TCF1+PD-1+ progenitor exhausted CD8 T cells (Tpex) can self-renew and give rise to Tim-3+PD-1+ terminally differentiated CD8 T cells that retain their effector functions. Tpex cells are thus essential to maintaining a pool of antigen-specific CD8 T cells during persistent antigenic stimulation, and only they respond to PD-1-targeted therapy. Despite their potential as a crucial therapeutic target for immune interventions, the mechanisms controlling the maintenance of virus-specific Tpex cells remain to be determined. We observed approximately 10-fold fewer Tpex cells in the spleens of mice chronically infected with lymphocytic choriomeningitis virus (LCMV) one-year post-infection (p.i.) than at three months p.i. Similar to memory CD8 T cells, Tpex cells have been found to undergo self-renewal in the lymphoid organs, prominently the bone marrow, during chronic LCMV infection. Furthermore, ex vivo treatment with IL-15 preferentially induced the proliferation of Tpex cells rather than the terminally differentiated subsets. Interestingly, single-cell RNA sequencing analysis of LCMV-specific exhausted CD8 T cells after ex vivo IL-15 treatment compared with those before treatment revealed increased expression of ribosome-related genes and decreased expression of genes associated with the TCR signaling pathway and apoptosis in both Tpex and Ttex subsets. The exogenous administration of IL-15 to chronically LCMV-infected mice also significantly increased self-renewal of Tpex cells in the spleen and bone marrow. In addition, we assessed the responsiveness of CD8 tumor-infiltrating lymphocytes (TILs) from renal cell carcinoma patients to IL-15. Similar to the data we obtained from chronic viral infection in mice, the expansion of the Tpex subset of PD-1+ CD8 TILs upon ex vivo IL-15 treatment was significantly higher than that of the terminally differentiated subset. These results show that IL-15 could promote self-renewal of Tpex cells, which has important therapeutic implications.